2006
DOI: 10.1104/pp.105.073957
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, Productivity, and Yield of Maize Are Not Affected by Open-Air Elevation of CO2 Concentration in the Absence of Drought

Abstract: (A.R.) While increasing temperatures and altered soil moisture arising from climate change in the next 50 years are projected to decrease yield of food crops, elevated CO 2 concentration ([CO 2 ]) is predicted to enhance yield and offset these detrimental factors. However, C 4 photosynthesis is usually saturated at current [CO 2 Global climate change, in the form of rising temperature and altered soil moisture, is projected to decrease the yield of food crops over the next 50 years (Thomson et al., 2005).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
378
5
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(415 citation statements)
references
References 61 publications
26
378
5
6
Order By: Relevance
“…This hypothesized mechanism is consistent with studies investigating the effects of elevated atmospheric pCO 2 (55-70 Pa) on the water relations of C 4 plants, where reduced g s and E improve plant and soil water status, and extend the active period for photosynthesis and growth (Ghannoum et al, 2000). This indirect effect of elevated pCO 2 is particularly important when C 4 plants experience some kind of water deficit (Conley et al, 2001;Wall et al, 2001;Leakey et al, 2004Leakey et al, , 2006Leakey, 2009). It seems likely that these feedbacks of water status on stomatal conductance, and hence photosynthesis, should be greater at sub-ambient than elevated pCO 2 .…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…This hypothesized mechanism is consistent with studies investigating the effects of elevated atmospheric pCO 2 (55-70 Pa) on the water relations of C 4 plants, where reduced g s and E improve plant and soil water status, and extend the active period for photosynthesis and growth (Ghannoum et al, 2000). This indirect effect of elevated pCO 2 is particularly important when C 4 plants experience some kind of water deficit (Conley et al, 2001;Wall et al, 2001;Leakey et al, 2004Leakey et al, , 2006Leakey, 2009). It seems likely that these feedbacks of water status on stomatal conductance, and hence photosynthesis, should be greater at sub-ambient than elevated pCO 2 .…”
Section: Introductionsupporting
confidence: 71%
“…This means that we cannot exclude the possibility of carry-over effects from one cycle to the next, or ontogenetic effects as the plants developed (Harb et al, 2010;Walter et al, 2011). However, the patterns observed from one cycle to the next were internally consistent overall, and consistent with mechanisms of CO 2 -water interactions observed previously (Conley et al, 2001;Wall et al, 2001;Leakey et al, 2004Leakey et al, , 2006Leakey, 2009). Secondly, because our interest was in how physiological characteristics vary over a short experimental watering cycle, we investigated changes over time and did not use a control on a shorter watering cycle.…”
Section: Discussionmentioning
confidence: 47%
“…A major motivation for the above effort is the high rate of human-accelerated environmental change, including elevated atmospheric ozone, CO 2 , nitrogen deposition, climate change and land use/land cover change [33,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][129][130][131][132]. It is a clear fact that these changes can affect mycorrhizal fungal species, but it is also clear that we do not yet have data sets sufficiently saturated, or models sufficiently powerful, to determine the exact nature, timing and spatial pattern of fungal community responses.…”
Section: Microbiological Methodologies: Mycorrhizal Fungal Community-mentioning
confidence: 99%
“…Plants live in soil-plant-atmosphere continuum (SPAC) environment, and they have to coordinate the mechanisms of diverse types to respond to the above changing environment at any time for sustainable survival [4][5][6][7][8][9][21][22][23][24][25][26][27][28][29][47][48][49][50][51][52][53][54][55][56][57][58][59]. Plant production realization is obtained eventually through physiological pathways at least at the level of individual and community [102][103][104][105][106][107][108][109]120,[130][131][132][133][134][135][136][137][138][139][140].…”
Section: Physiological Theories: Understanding Higher Plant Physiologmentioning
confidence: 99%
“…Elevated CO 2 (eCO 2 ) concentration in the atmosphere is an additional factor that is not accounted for in this study, due to the uncertainty of the effects at present. There is substantial evidence that eCO 2 results in increased yield and both above-and belowground biomass in most crops (Dijkstra and Morgan 2012), although this effect appears to vary in maize, showing increases in studies in China and India (Xie et al 2015;Abebe et al 2016), and no response in maize in Illinois unless under drought stress (Leakey et al 2006;Dijkstra and Morgan 2012;Attavanich and McCarl 2014). Another study found increased biomass response in maize under drought stress, but only where there was a sufficient supply of nitrogen (N) (Zong and Shangguan 2014).…”
Section: Bulk Density (Mg Mmentioning
confidence: 99%